A new Vietnamese species of Euconnus (Napochus) with modified antennal club (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł; Nomura, Shûhei (Zootaxa, 2018)
Napochus Thomson, 1859 is the largest subgenus of Euconnus Thomson, 1859, currently comprising over 300 nominal species (Newton & Franz 1998; Jałoszyński 2015, 2016, 2017a, b). The subgenus was recently redefined and its adult morphological structures were illustrated and described in detail (Jałoszyński 2015). Moreover, the subgenera Neonapochus Machulka, 1929, Paranapochus Franz, 1986, Smicrophus Casey, 1897, Cephaloconnus Franz, 1998 and Cerviconnus Franz, 1962, and a genus Protoscydmus Franz, 1992 were placed as junior synonyms of Napochus (Jałoszyński 2015, 2016, 2017a, b). Currently Napochus is defined mainly by the subtrapezoidal pronotum, which is always broadest behind middle (typically at base or shortly in front of base) and strongly narrowed anterad, so that its anterior margin is much shorter than the posterior margin; and by the tetramerous antennal club. The latter, however, may be indistinctly tetramerous in some species, with the antennomere VIII only slightly larger than VII; antennae in such beetles may appear gradually broadened or even trimerous. The problem of antennal variability within Napochus requires further studies, and it is possible that the number of antennomeres forming the club should be excluded from the diagnosis, as too variable. Until recently, species of Euconnus similar to the type species of Napochus and with unmodified antennomeres were placed in Napochus, and one species, in which males have the antennal club modified, in a subgenus Neonapochus. Also beetles resembling Napochus but showing a sexual dimorphism in the head capsule (with cavities, impressions or unusual concavities in males) were placed not in Napochus, but in Cephaloconnus. Jałoszyński (2016, 2017b) demonstrated that beetles showing such modifications do not differ from Napochus in any important characters, and synonymized Neonapochus and Cephaloconnus with Napochus.